Bacterial and Fungal Infections Promote the Bone Erosion Progression in Acquired Cholesteatoma Revealed by Metagenomic Next-Generation Sequencing - Jiang, Hua; Wu, Chengpeng; Xu, Jingjie; Wang, Qi; Shen, Lei; Ou, Xunyan; Liu, Hongyan; Han, Xu; Wang, Jun; Ding, Wenchao; Hu, Lidan; Chen, Xiangjun (Frontiers in Microbiology, 2021)
An acquired cholesteatoma generally occurs as a consequence of otitis media and eustachian tube dysfunction. Patients with acquired cholesteatoma generally present with chronic otorrhea and progressive conductive hearing loss. There are many microbes reportedly associated with acquired cholesteatoma. However, conventional culture-based techniques show a typically low detection rate for many bacteria and fungi. Metagenomic next-generation sequencing (mNGS), an emerging powerful platform, offers higher sensitivity and higher throughput for evaluating many samples at once, remains to be studied in acquired cholesteatoma. In this study, 16 consecutive patients from January 2020 to January 2021 at the Second Affiliated Hospital of Zhejiang University School of Medicine (SAHZU) were reviewed. We detected a total of 31 microbial species, mNGS provided a higher detection rate compared to culture (100% vs 31.25%, p=0.000034) in patients. As the severity of the patient's pathological condition worsens, the more complex the types of microbes’ infections. The most commonly detected microbial genus was Aspergillus (9/16,56.25%), especially in patients with severe bone erosion. In summary, mNGS enhances our ability to identify pathogens of cholesteatoma patients, and Aspergillus infections increase bone destruction in acquired cholesteatoma.